Daily adaptive radiotherapy for patients with prostate cancer using a high field MR-linac: Initial clinical experiences and assessment of delivered doses compared to a C-arm linac. (July 2020) - Dunlop, Alex; Mitchell, Adam; Tree, Alison; Barnes, Helen; Bower, Lorna; Chick, Joan; Goodwin, Edmund; Herbert, Trina; Lawes, Rebekah; McNair, Helen; McQuaid, Dualta; Mohajer, Jonathan; et al.
Highlights: MR-guided radiotherapy for prostate cancer can be delivered using a high filed MR-linac. Comparison of estimated delivered dose between MR-guided adapted radiotherapy and conventional C-arm techniques. MR-guided adaptive radiotherapy demonstrates improved target coverage for a subset of prostate cancer patients. Abstract: Introduction: MR-guided adapted radiotherapy (MRgART) using a high field MR-linac has recently become available. We report the estimated delivered fractional dose of the first five prostate cancer patients treated at our centre using MRgART and compare this to C-Arm linac daily Image Guided Radiotherapy (IGRT). Methods: Patients were treated using adapted treatment plans shaped to their daily anatomy. The treatments were recalculated on an MR image acquired immediately prior to treatment delivery in order to estimate the delivered fractional dose. C-arm linac non-adapted VMAT treatment plans were recalculated on the same MR images to estimate the fractional dose that would have been delivered using conventional radiotherapy techniques using a daily IGRT protocol. Results: 95% and 93% of mandatory target coverage objectives and organ at risk dose constraints were achieved by MRgART and C-arm linac delivered dose estimates, respectively. Both delivery techniques were estimated to have achieved 98% of mandatory Organ At Risk (OAR) dose constraints whereas for the target clinical goals, 86% and 80% were achieved by MRgART and C-arm linac delivered dose estimates. Conclusions: Prostate MRgART can be delivered using the a high field MR-linac. Radiotherapy performed on a C-arm linac offers a good solution for prostate cancer patients who present with favourable anatomy at the time of reference imaging and demonstrate stable anatomy throughout the course of their treatment. For patients with critical OARs abutting target volumes on their reference image we have demonstrated the potential for a target dose coverage improvement for MRgART compared to C-arm linac treatment.